Analisis Maslahat Imam al-Ghazali dalam Penahanan Akta Cerai sebagai Upaya Jaminan Perlindungan Hak-hak Perempuan Setelah Perceraian - Siti Fauzizah (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
This study aims to analyze Imam al-Ghazali's maslahat view of the provision of withholding divorce certificates as a government effort to ensure the protection of women's rights after a contested divorce. This research uses normative juridical methods which include library research by examining library materials or secondary data sources with data collection techniques using the istislahi approach. The results of the study show that the instrument of the Supreme Court's Religious Justice Agency Letter Number 1960/DJA/HK.00/6/2021 is an information accessibility to guarantee women's rights after divorce, especially a contested divorce, in the form of withholding the Defendant's divorce certificate until he meets the Plaintiff's demands, which can be included when making a divorce suit. This letter is a policy that regulates the smooth administration of justice, it is not binding but has legal relevance to achieve benefits. Regarding the determination of maintenance after a contested divorce (divorce bain) which has not been regulated, but as legal events develop, it may be determined as long as the wife is not proven to be nusyuz and the woman who files for a contested divorce is considered an oppressed party and is at risk of being vulnerable so that it should be protected to preserve her soul as one of the objectives of Islamic law. However, from the aspect of implementation, there is no grace period for fulfillment, so there is no legal certainty in the fulfillment of the plaintiff's demands and the benefit is not achieved.